Marketing Audit as a Tool for Assessing Business Performance - FESHCHUR, Iryna; HURZHYI, Nataliia; KUZMINSKA, Yuliia; DANCHENKO, Olena; HORIASHCHENKO, Yuliia (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
The aim of this article is to determine an approach to the practical implementation of a marketing audit of business performance in a competitive environment. The aim will be achieved with the involvement of the following methods: trend, comparative and rating analyses, the BCG matrix, the Brand Health Tracking, and Delfi methods. As a result of the conducted research, an approach to conducting a marketing audit of business performance in a competitive environment with an emphasis on the use of modern digital platforms and web resources was proposed. The proposed approach to the implementation of a marketing audit of business performance in a competitive environment involved the use of the BCG matrix to determine the positions of the four leading confectionery companies of Ukraine in terms of revenue volume and growth, as well as the market share. The online presence analysis evaluated the online presence of the studied companies and to analyse other related indicators. The conducted analysis gave grounds to provide relevant recommendations. The importance of implementing each of them was determined with the help of the Delphi method. The obtained results can be applied in practice in the activities of companies in order to improve the approach to the implementation of marketing audit as a tool for assessing business performance in a competitive environment. Academic novelty is the developed comprehensive practical approach to the implementation of marketing audit as a tool for assessing business performance relative to competitors using modern digital platforms.